Scientific American. – 1869. – Vol. 21, № 9 - б/а (New York. Munn & Company, 1869)
A weekly journal of practical information, art, science, mechanics, chemistry and manufactures.
Keywords: Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of science and ideas; Research Subject Categories::HUMANITIES and RELIGION::History and philosophy subjects::History subjects::History of technology and industry; Research Subject Categories::SOCIAL SCIENCES::Other social sciences::Mass communication; August 28, 1869